Dynamical mean field theory with the density matrix renormalization group - Garcia, Daniel Julio (2004)
A new algorithm to solve the dynamical mean field theory (DMFT) equations of strongly correlated models exploiting the DMRG methodology was presented. The methods uses the density matrix renormalization group technique to solve the associated impurity problem. In contrast with NRG, this algorithms deals with all energy scales on equal footing, which allowed to find substructure in the Hubbard bands of the correlated metallic state. It was observed that with this algorithm, more complex models having a large number of degrees of freedom could be considered and finite-size effects could be minimized.